Are schools replaceable? Creative destruction in the post-pandemic society - Narodowski, Mariano; Campetella, Maria Delfina (Journal of Interdisciplinary Studies in Education, 2021)
Lockdown measures and school closures due to coronavirus have forced governments, schools, and teachers to find new ways to ensure learning continuity. Initiatives differ according to the country’s level of development and the socioeconomic status of students. The situation has exposed and has amplified the relationship between wealth and richer home learning environments and is also evidencing and magnifying the digital divides between students and between schools. Simultaneously, innovation processes seem to be occurring in response to the restriction measures. The purpose of this short essay is to discuss the consequences of COVID-19 on students, pedagogy, and schools, particularly the relationship between socioeconomic conditions and possibilities of innovation in education. Based on Schumpeter’s concept of creative destruction we suggest that while some institutions may have the possibility of reconverting themselves by developing blended models of education, for a vast worldwide majority of students, traditional – face-to-face and disconnected – schools are irreplaceable.